Integrating Faith, Knowledge, and Action in Islamic Education - Fitrah Nurul Husna; Elihami (Al-Mirah: Jurnal Pendidikan Islam, 2026)
The integration of faith, knowledge, and action is a fundamental principle in Islamic education that aims to develop individuals holistically by balancing spiritual, intellectual, and practical dimensions of life. This concept emphasizes that faith (iman) serves as the foundation of belief and moral guidance, knowledge (ilm) functions as a means of understanding and navigating life, and action (amal) represents the practical manifestation of faith and knowledge. The purpose of this paper is to examine the significance of integrating these three elements within the framework of Islamic education and their role in shaping responsible, ethical, and productive individuals. Using a descriptive and conceptual approach, the study explores the interrelationship among faith, knowledge, and action based on Islamic teachings and educational principles. The findings indicate that faith provides direction and purpose, knowledge enhances understanding and decision-making, and action transforms beliefs and knowledge into meaningful contributions to society. The study further highlights that effective Islamic education should not focus solely on academic achievement but also on character formation, moral development, and social responsibility. The integration of faith, knowledge, and action contributes to the development of balanced individuals who are capable of addressing contemporary challenges while maintaining strong spiritual values. Therefore, educational institutions, families, and communities should collaborate in promoting this integrated approach to ensure the cultivation of competent, ethical, and socially responsible generations. Ultimately, the harmonious integration of faith, knowledge, and action serves as a foundation for achieving success in both worldly life and the hereafter.